Fitness periodization for the developmental skater - Kashubara, K. (The Professional Skater PS Magazine, 2015)
The National Strength and Conditioning Association (NSCA) recommends that figure skaters follow these periodization phases: • Active Rest • Preseason • Offseason • In Season • Taper • Major Competition This progression allows the International-level skater to peak, athletically, for the Olympics or World competitions. It allows developmental figure skaters to peak for regional, sectional or national competitions. The juvenile level figure skater, for example, induces many challenges for the off-ice professional. First and foremost is the age. The youth athletes body is going to be more linear than adults. The youths are growing taller. These elements of change disrupt the center of gravity, posture, and coordinative abilities. Even developmental junior-level skaters present challenges. While most of them will not grow much taller, they are not used to their newfound stature, or the height of their jumps. They also might be struggling with endurance because of longer programs and the added adult weight. The adult athlete has their sights set on where they are going. The youth athlete is just trying to figure out where they are.